2021
DOI: 10.1002/jum.15884
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Ultrasound Detects Vocal Fold Immobility in Adults

Abstract: Laryngeal ultrasound (US) is becoming widely accepted for assessing true vocal fold immobility (TVFI), a potential complication of laryngeal and thyroid surgery. The objective of this project is to perform a systematic review and meta‐analysis of pooled evidence surrounding laryngeal US as a modality for diagnosing TVFI in adults at risk for the condition in comparison to laryngoscopy as a gold standard. Medical subject heading terms were used to search MEDLINE, Embase, Google Scholar, Web of Science, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Ultrasound assessment of laryngeal function via TLUS has been described extensively within the literature in post-thyroidectomy populations (Allen et al, 2021;Beale et al, 2020;Dedecjus et al, 2010;Fung & Lang, 2021;Gambardella et al, 2020;Knyazeva et al, 2018;Nasser et al, 2020;Noel et al, n.d.;A. Patel et al, 2021;Rybakovas et al, 2019;Su et al, 2022), and has been found to have high sensitivity as a screening tool for vocal fold palsy. It is also described as a valid and reliable real-time diagnostic tool (Allen et al, 2021;Nasser et al, 2020;A.…”
Section: Prevalencementioning
confidence: 99%
“…Ultrasound assessment of laryngeal function via TLUS has been described extensively within the literature in post-thyroidectomy populations (Allen et al, 2021;Beale et al, 2020;Dedecjus et al, 2010;Fung & Lang, 2021;Gambardella et al, 2020;Knyazeva et al, 2018;Nasser et al, 2020;Noel et al, n.d.;A. Patel et al, 2021;Rybakovas et al, 2019;Su et al, 2022), and has been found to have high sensitivity as a screening tool for vocal fold palsy. It is also described as a valid and reliable real-time diagnostic tool (Allen et al, 2021;Nasser et al, 2020;A.…”
Section: Prevalencementioning
confidence: 99%
“…SWE has been used to evaluate normal mechanical properties (stiffness) of skeletal muscles, and the change in increased passive muscle stiffness with stretched muscles. 11 There are a few reports of using ultrasound elastography (SWE and strain imaging) to assess FVF. 12 We aimed to investigate the feasibility of SWE for evaluation of mechanical properties, function, and symmetry in adult FVF with age.…”
mentioning
confidence: 99%
“…Ultrasound imaging is not only beneficial in the sense that it provides a real‐time image for motion, but it also reduces the need for more invasive modalities to assess tissue functionality such as invasive transesophageal imaging of the larynx or surgical biopsy for histological assessment of FVF tissue. SWE has been used to evaluate normal mechanical properties (stiffness) of skeletal muscles, and the change in increased passive muscle stiffness with stretched muscles 11 . There are a few reports of using ultrasound elastography (SWE and strain imaging) to assess FVF 12 .…”
mentioning
confidence: 99%